Estudio de confiabilidad en la subestación Quevedo de cnel ep. Unidad de negocio Santo Domingo - Tacle Mora, Leyton Fernando (2019)
This project details criteria and methodologies of reliability assessment in a distribution substation, for this purpose and applicability the E/S Quevedo of CNEL EP. was considered Santo Domingo Business Unit. In the first instance, information was collected on all faults and contingencies at the substation in mention, allowing all those with duration times longer than three minutes to be classified and taken into account as established by regulation No. ARCONEL 005/18, once the outages were counted, the failure and repair rates were calculated, with the forced availability (A) and forced unavailability (U) of each device , then the overall reliability of the entire S/E was determined using the deterministic technique called network reduction resulting in a forced availability of 0,7282 at the 13.8 kV buses of each transformer. Result that was tested by simulating Monte Carlo in the MATLAB computer package, whose result was 0,7292.